Seismic hazard assessment of eastern Nepal using 1934 and 1988 earthquakes - Chamlagain, Deepak; Bhattarai, Ganesh Kumar; Rajaure, Sudhir (Journal of Nepal Geological Society, 2011)
The Himalayan arc is widely considered as one of the hot spots in terms of earthquake disaster. Nepal, which is centrally located in the Himalayan region, has witnessed many medium to large earthquakes in the past, e.g., 1934 Bihar-Nepal earthquake, 19 88 Udayapur earthquake. Because of lack of income resources in rural area, considerable number of population has already migrated to the major urban areas of the country and the trend is still continued. With such population pressure and also economic constrains, major part of population is residing in weak and non-engineered structures of the unplanned urban areas. Consequently, it has put large population at high risk of earthquake disaster. It is, therefore, necessary to assess the seismic hazard so that proper mitigation measures may be adopted for the safeguard of the population, property and infrastructures under risk. In this contribution, preliminary Probabilistic Seismic Hazard Analysis (PSHA) for eastern Nepal is carried out taking two point sources, i.e. 19 3 4 Bihar -Ne pal and 1988 Udayapur earthquakes. For Bihar-Nepal earthquake Peak Ground Acceleration (PGA) of 100 gal is computed for southeastern Nepal and exceeds as much as 350 gal near the epicenter. The 1988 Udayapur earthquake having smaller magnitude than 1934 Bihar Nepal earthquake has given maximum 300 gal of PGA. The computed intensities for both earthquakes almost correspond with the observed values. The study, for the first time, provides strong ground motion data at local level and may be useful in designing engineering structures, upgradation of building code and most importantly to formulate policy for earthquake risk management in eastern Nepal.